Awareness regarding Thyroid Hormone Disorder among Women of Pokhara - Acharya, Isha; Sharma, Sunita; Tiwari, Sirjana (Nepal Journal of Medical Sciences, 2024)
Introduction: Thyroid disorders were increasingly recognized as a significant health issue in Nepal, particularly among females, mirroring global concerns. Despite the prevalence of symptoms, many Nepalese women remain unaware of thyroid disorders. This study aimed to assess the awareness levels regarding thyroid hormone disorders among women in Pokhara Metropolitan City-19. Methods: A cross-sectional study was conducted from May to October 2021, involving 222 female residents of Pokhara Metropolitan City-19. Data were collected using a semi-structured interview tool through face-to-face interviews. The chi-square test was used to examine associations between dependent and independent variables. Ethical approval was obtained from the institutional review committee at Pokhara University and the ward office, and verbal and written informed consent was obtained from all the participants. Results: Out of the 222 respondents, 137 (61.71%) demonstrated an accurate knowledge on thyroid. Among those with a personal history of thyroid hormone disorder, 40 (18.02%) exhibited 100% adequate awareness. Significant associations (p<0.05) were observed between awareness levels and sociodemographic variables such as respondent age and family members employed in health-related fields. Conclusions: The majority of respondents demonstrated accurate knowledge, and less than half exhibited inaccurate knowledge regarding thyroid hormone disorders. This highlights the necessity for educational programs and awareness campaigns targeting the general population of Pokhara Metropolitan City-19.